Ripple effects of COVID-19 lockdown pertaining to clinical skills among undergraduate medical students of Karachi - Asma Shaikh; Mawara Amin; Azhar Uddin; Mahrukh Khan; Muhammad Ammad Hussain; Ubaid Ahmed Khan (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the outcomes of coronavirus disease-2019 lockdown pertaining to clinical skills among undergraduate medical students. Method: The cross-sectional questionnaire-based study was conducted after approval from the Jinnah Sindh Medical University, Karachi, at 6 public and private medical education institutions in Karachi from July 3 to August 3, 2021, and comprised undergraduate students from the 3rd, 4th and final academic years. Data was collected using a pre-designed questionnaire. Data was analysed using SPSS 20. Results: Of the 383 subjects, 260(67.9%) were females and 123(32.1%) were males. The overall age range was 20-25 years. There were 145(37.9%) students from the 3rd year, 154(40.2%) from 4th and 84(21.9%) from the final year. Among them, 251(84.2%) accepted having decreased efficiency in clinical skills because they were not being able to train in person, 157(41%) claimed that certain topics related to clinical study were given in exams even though they were not taught, and 164(72.6%) faced difficulty in exams related to clinical skills. Conclusion: Coronavirus disease-2019 caused disruption in routine life, and medical education was not an exception. E-learning modality was found to be insufficient, and patient exposure elevates confidence, eliminates hesitation, and improves clinical skills. Key Words: COVID-19, Clinical skills, Undergraduate medical students.